The use of transgenics in the laboratory axolotl. Issue 6 (13th May 2021) - Tilley, Lydia; Papadopoulos, Sofia‐Christina; Pende, Marko; Fei, Ji‐Feng; Murawala, Prayag
Abstract: The ability to generate transgenic animals sparked a wave of research committed to implementing such technology in a wide variety of model organisms. Building a solid base of ubiquitous and tissue‐specific reporter lines has set the stage for later interrogations of individual cells or genetic elements. Compared to other widely used model organisms such as mice, zebrafish and fruit flies, there are only a few transgenic lines available in the laboratory axolotl ( Ambystoma mexicanum ), although their number is steadily expanding. In this review, we discuss a brief history of the transgenic methodologies in axolotl and their advantages and disadvantages. Next, we discuss available transgenic lines and insights we have been able to glean from them. Finally, we list challenges when developing transgenic axolotl, and where further work is needed in order to improve their standing as both a developmental and regenerative model. Key Findings: This manuscript covers the history of transgenic applications in Ambystoma mexicanum. Different transgenic systems allows for different kinds of biological study, and we discuss some of the larger insights that have been made using these axolotl lines. Finally, we touch upon the challenges inherent with an axolotl research lab, and highlight where in the field additional research is needed.